Synthesis and characterization of soluble conducting polymers for optoelectronic applications / Hammed Wasiu Adebayo - Hammed Wasiu, Adebayo (2017)
Accelerated increase in growth of world energy consumption, the fast depletion of fossil fuel reserve and climatic change due to the burning of fossil fuel have called for sourcing alternative means to generate energy. Renewable energy sources are inexhaustible and occur naturally; the energy generated are non-polluting and economically viable thus, they are believed to be the befitting alternatives to nonrenewable fossil fuels. The most salient method of exploiting the solar energy is via solar cells which directly convert solar radiation absorbed by semiconductors to electrical energy. Unlike silicon solar cells, polymer solar cells are solution processed, flexible and lightweight and therefore believed to offer the eventual solution to renewable energy. Challenges such as low power conversion efficiency and durability being overcome have made polymer solar cells suitable candidate for a future energy source. Backbone rigidity prevents many conjugated polymers from being processable from organic solvents creating major hindrances to their potential applications as donor materials for polymer photovoltaics. Side-chain functionalization is a common way of rendering conjugated polymers solution processed, however, factors such a structural modification can cause steric hindrance in the polymer molecule. Therefore, electrical, optical and mechanical properties of the polymers are greatly affected. Dodecyl benzene sulfonic acid, a surfactant anion, has been used to improve solubility of conducting polyaniline (PANI) and polypyrrole (Ppy) making them soluble in m-cresol, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and chloroform. This thesis addresses the use of DBSA as a dopant and stabilizer for the synthesis of solution processed conducting polymers. The materials studied in this project are intended for donor material in the active layer of polymer solar cells. Meanwhile, chemical oxidative polymerization of processable conducting polypyrrole using DBSA, a relatively large dopant anion, reduces intermolecular interaction between polypyrrole chains, leading to the organic soluble Ppy. Therefore, in the present study, solution processable copolymer containing PNVC and Ppy was synthesized via chemical oxidative polymerization with DBSA as a dopant and stabilizer and ammonium persulfate the oxidant. It was found that the solubility of the resulting copolymer was greatly enhanced by the DBSA dopant. Furthermore, the result from the electrical and thermal analysis showed improved thermal behaviour with respect to the Ppy and electrical conductivity as regards the PNVC. Additionally, photovoltaic properties of the DBSA dope PNVC-Ppy copolymer was tested by fabricating BHJ solar cell using the copolymer product as the donor and a soluble fullerene derivative PC60BM as the acceptor. The effect of GO and rGO on the electrical properties of the DBSA-doped PNVC-Ppy copolymer was further investigated due to the fact that π-electron rich polymers can form π-stacking with the graphene sheets. The obtained nanocomposites exhibited appropriate optical and electrical properties to be used an active layer in polymer electronics. In conclusion, this thesis demonstrates that solubility of the PNVCPpy copolymer can be significantly improved by doping with DBSA and the doped copolymer can be applied in photovoltaics.